UPAYA PENINGKATAN KUALITAS PAUD PUTIH MELATI KELURAHAN MERGOSONO KECAMATAN KEDUNGKANDANG MALANG MELALUI PENDIDIKAN ANAK USIA DINI DAN PENINGKATAN KUALITAS PENDIDIK - Nilawati F; Baroroh L; Farika N; Achmad Z; Yosi A (Jurnal Pengabdian Polinema Kepada Masyarakat, 2020)
In Indonesia, the age between 0-6 years is agreed, which is explained in article 28 of the Law on the National Education System no. 20 of 2003 paragraph 1 explained that "early childhood is a child who falls in the age range of 0-6 years". Thus it can be stated that early childhood is a child in the range of 0-6 years who have growth and development according to their characteristics. In Mergosono Sub-District, Kedungkandang District, there are 6 (six) Pos PAUD. Pos PAUD Putih Melati is one of the Pos PAUD located in RW 1, Mergosono Sub-District, Kedungkandang District. This Pos PAUD was created with the aim of meeting the needs of the surrounding community, especially with regard to early childhood education. So far, Pos PAUD have been managed more based on principles from, by and for the community. The method used in this PkM is the transfer of knowledge and discussion of problems. The implementation of activities in the form of management training and financial administration of Pos PAUD, procurement of Educational Game Equipment (APE), procurement of APE storage lockers, and procurement of Pos PAUD financial administration books. Financial Management and Administration Training for the managers of Pos PAUD Putih Melati was the result of the initial discussion. Based on the results of the discussion it was found that the Pos PAUD Putih Melati manager experienced obstacles in terms of financial management and administration. Therefore, dedication was carried out in the form of providing material related to the management and financial administration of Pos PAUD Putih Melati. Overall, the service activities carried out at the Pos PAUD Putih Melati can be said to be successful. This success is not only measured by the four components above, it can also be seen from the participants' satisfaction after participating in the activities and the use of APE by students of the Pos PAUD Putih Melati. Based on the results of the implementation of the dedication that has been carried out, several suggestions can be submitted, namely: 1) The time of the implementation of the service activities needs to be increased so that the objectives of the activity can be fully achieved. 2) The existence of follow-up activities in the form of similar training is always held periodically so as to improve the ability of teachers to carry out the teaching and learning process.